Oncorequisite role of an aldehyde dehydrogenase in the pathogenesis of T-cell acute lymphoblastic leukemia - Zhang, Chujing (Haematologica, 2020)
Aldehyde dehydrogenases (ALDH) are overexpressed in various types of cancers. One of the ALDH family genes, ALDH1A2, is aberrantly expressed in more than 50% of cases of T-cell acute lymphoblastic leukemia (T-ALL). However, its molecular function and role in the pathogenesis of T-ALL are largely unknown. Chromatin immunoprecipitation-sequencing and RNA-sequencing analyses showed that the oncogenic transcription factor TAL1 and its regulatory partners bind to the intronic regulatory element of the ALDH1A2 gene, directly inducing a T-ALL-specific isoform with enzymatic activity. ALDH1A2 was preferentially expressed in the TAL1-positive T-ALL subgroup. In TALL cell lines, depletion of ALDH1A2 inhibited cell viability and induced apoptosis. Interestingly, gene expression and metabolomic profiling revealed that ALDH1A2 supported glycolysis and the tricarboxylic acid cycle, accompanied by NADH production, by affecting multiple metabolic enzymes to promote ATP production. Depletion of ALDH1A2 increased the levels of reactive oxygen species, while the levels were reduced by ALDH1A2 overexpression both in vitro and in vivo. Overexpression of ALDH1A2 accelerated tumor onset and increased tumor penetrance in a zebrafish model of T-ALL. Taken together, our results indicate that ALDH1A2 protects against intracellular stress and promotes T-ALL cell metabolism and survival. ALDH1A2 overexpression enables leukemic clones to sustain a hyper-proliferative state driven by oncogenes.